How Fishery Collapses: The Case of Lepidopus caudatus (Pisces: Trichiuridae) in the Strait of Sicily (Central Mediterranean) - Falsone, Fabio; Scannella, Danilo; Geraci, Michele Luca; Gancitano, Vita; Vitale, Sergio; Fiorentino, Fabio (Frontiers in Marine Science, 2021)
The silver scabbardfish Lepidopus caudatus (Euphrasen, 1788) is a mesopelagic species living on the shelf and slope down to 600 m in temperate seas all around the world. In the Mediterranean, the species is caught mainly by longlines with a marked seasonality. In the early nineties in the Strait of Sicily (Central Mediterranean Sea), a new fishery targeting L. caudatus was developed. This fishery uses an ad hoc a pelagic trawl gear called 'spatolara'. Vessels using spatolara have increased from one in 1993 to ten in 2007 with a growth of catches up to 1,200 tons in 2011. Development of this fishery was not regulated by any specific management measures and, due to the progressive reduction of catch to 169 tons, only one vessel was active in 2018. The availability of catch and biomass indices from trawl survey since the beginning of trawling exploitation, allowed to provide the first assessment of the state of L. caudatus stock in the Central Mediterranean (GFCM Geographical Sub-Area 16) by using data limited methods. Catch-Maximum Sustainable Yield (CMSY) and Bayesian State Space Schaefer model (BSM), were fitted to landings and abundances indices (2004 -2018). The Abundance Maximum Sustainable Yield model (AMSY) was also applied to survey data from 1994 (one year after the start of the spatolara fishery) to 2018 to further corroborate the results. BSM prediction of biomass levels was just above 50% of BMSY, whereas AMSY estimated the current stock levels below 50% of BMSY. The BSM was used for forecasting B/BMSY and catches under different fishing scenarios. Although current exploitation was very close to FMSY, more than a decade would need to rebuild the stock to biomass levels producing MSY. A faster rebuilding could be achieved fishing at least 80% of FMSY, with minimal loss in yield over the next 5 to 8 years. Following the development of a new fishery since the beginning, the study provides a further example of how unregulated exploitation lead to a heavy overfished state of stock and collapse of fishing activities.